Reflections on the Eurozone’s Challenges - Marta Götz (Contemporary Economics)
This paper considers the primary challenges faced by the Eurozone and caused by the 2008+ crisis. It suggests that one should distinguish among institutional, conceptual (model/paradigm) and real economic challenges. As a factor that influences progress in other areas, the latter topic is a special focus. It shall be stressed that the classification advanced in this paper is only one of many possibilities. The division into three groups may help navigate the discussion on problems that are occurring or likely to occur in the Eurozone. However, the intertwined character of these challenges and their interdependence is also stressed. Generally, it seems reasonable to agree that the institutional and conceptual challenges will persist and that no easy solution can be expected soon. A simple evaluation of the Eurozone’s macroeconomic stability based on available forecasts results in several tentative, overly optimistic conclusions that a slightly increasing internal cohesion is underway. More macroeconomic harmony can be expected. However, bold institutional reforms are required.